Materiality and external assurance in corporate sustainability reporting: An exploratory study of Europe's leading commercial property companies. Issue 2 (1st August 2016) - Jones, Peter; Hillier, David; Comfort, Daphne
Abstract : Purpose: The purposes of this paper are to provide a preliminary examination of the extent to which Europe's leading commercial property companies are embracing the concept of materiality and commissioning independent external assurance as part of their sustainability reporting processes and to offer some wider reflections on materiality and external assurance in sustainability reporting. Design/methodology/approach: The paper begins with an introduction to corporate sustainability, an outline of the European property market and of the drivers for, and challenges to, sustainability for property companies and a review of the characteristics of materiality and external assurance. The information on which the paper is based is drawn from the leading European commercial property companies' corporate websites. Findings: The paper reveals that all of Europe's leading property companies had either reported or provided information on sustainability but that only approximately half of these companies had embraced materiality or commissioned some form of independent external assurance as an integral part of their sustainability reporting processes. In many ways, this reduces the reliability and credibility of the leading property companies' sustainability reports. Looking to the future, growing stakeholder pressure may force more of the leading European property companies to embrace materiality and commission external assurance as systematic and integral elements in the sustainability reporting process. Originality/value: The paper provides an accessible review of the current status of materiality and external assurance among Europe's leading commercial property companies' sustainability reporting and as such it will interest professionals, practitioners, academics and students interested in the sustainability in the property industry.